KEDUDUKAN ANAK ADOPSI DITINJAU DARI HAK PEWARISAN DI INDONESIA - Rangkuti, Feby Savira; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Already a nature of every human being in this world of the opposite sex to live together to continue the marriage and form a family that is happy with the goal of having offspring that human life is lost and can not be sustained .The desire to have a child is a human instinct , but the instinct is sometimes hampered by destiny , where the desire to have children is not reached. Adoption is an alternative to save marriage. The phenomenon of child adoption event is common in Indonesia society for both the outside and the family. Law number 1 of 1974 on the marriage does not regulate the issue of adoption or adoption agency but in customary law has been around a long time.In legal research, the researchers used a type of normative legal research. Methods of research in this paper is the research literature drawn from various sources of law. Source data used is primery data, secondary data and tertiary data.Research is the position adopted in the case of inheritance in Indonesia consists of 3 (three) legal systems, namely : customary law, positive law and Islamic law thethrid law has different rules of customary law requires each of the respective regions are some areas stipulate that adopted children have the same status as biological children in terms of inheritance and some areas do not provide equality in terms of inheritance so that adopted children are not entitled to inheritance. While the positive law stipulates that children adopted and biological children have the same position in terms of inheritance but are not regulated clearly in legislation and in Islamic law that arrangement contained in the law compilation islam states against adopted children who do not receive the inheritance given was borrowed as much 1/3 inheritance adoptive parents. The legal consequances of the adoption in terms of liability adoptive parents, they are required for the maintenance and education of the child until the child is capable of standing alone and adoptive parents be the legal guardian of the child since the court ruling setSuggestions writer , First , the government should establish a rule in the form of legislation or codification of the law governing the national adoption so that their legal certainty . Secondly , the need for socialization regarding child adoption so that attainment of the objectives of law and legal awareness in society in the implementation of child adoption .Keywords : The Position of The Child – Inheritance of Indonesia – Legal Consequences